2013
DOI: 10.3762/bjoc.9.140
|View full text |Cite
|
Sign up to set email alerts
|

Mild and efficient cyanuric chloride catalyzed Pictet–Spengler reaction

Abstract: SummaryA practical, mild and efficient protocol for the Pictet–Spengler reaction catalyzed by cyanuric chloride (trichloro-1,3,5-triazine, TCT) is described. The 6-endo cyclization of tryptophan/tryptamine and modified Pictet–Spengler substrates with both electron-withdrawing and electron-donating aldehydes was carried out by using a catalytic amount of TCT (10 mol %) in DMSO under a nitrogen atmosphere. TCT catalyzed the Pictet–Spengler reaction involving electron-donating aldehydes in excellent yield. Thus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 54 publications
0
12
1
Order By: Relevance
“…The THβCs ( 2a – 2h ) were obtained in poor to moderate yields. The steric hindrance and the presence of the electron-donating group at ortho position on the aromatic ring reduced the electrophilicity of aldehydes [ 44 ] and affected the yield of the THβC ring, while the less hindered electron donating group induced the cyclization to the THβC skeleton. The methyl ester substituent also increased the cyclization process.…”
Section: Resultsmentioning
confidence: 99%
“…The THβCs ( 2a – 2h ) were obtained in poor to moderate yields. The steric hindrance and the presence of the electron-donating group at ortho position on the aromatic ring reduced the electrophilicity of aldehydes [ 44 ] and affected the yield of the THβC ring, while the less hindered electron donating group induced the cyclization to the THβC skeleton. The methyl ester substituent also increased the cyclization process.…”
Section: Resultsmentioning
confidence: 99%
“…It has been proposed that guanidine group in a quaternary ammonium salt stabilizes the complex molecule through parallel interaction with substrate anions . It is well known that s‐triazine shows good catalytic performance in organic transformations, particularly in C−C and C−N bond formation and cyclization reactions . Recently, our research group has explored diversified uses of s ‐triazine as a starting material for the synthesis of new quaternary ammonium organocatalysts for enantioselective alkylation .…”
Section: Figurementioning
confidence: 99%
“…7 Sharma et al reported the one-pot synthesis of 4-aryl pyrrolo [1,2-a]quinoxalines from 1-(2-aminophenyl)pyrroles and aromatic aldehydes by a modified Pictet-Spengler reaction using cyanuric chloride. 8 Similarly, Verma et al reported the synthesis using AlCl 3 and benzotriazole (Scheme 1). 9 Pereira et al reported a one-pot synthesis using 1-(2nitrophenyl)pyrrole and an excess of alcohol under redox reaction conditions with iron (9 equiv) and 12 M hydrochloric acid (11 equiv).…”
mentioning
confidence: 97%
“…6 Pyrrolo [1,2-a]quinoxalines may be synthesized in two steps from 1-(2-aminophenyl)pyrroles. [7][8][9] Reaction of the 1-(2-aminophenyl)pyrrole with alkyl or aryl acid chlorides affords the corresponding acetamides, which, upon intramolecular cyclization under Bischler-Napieralski conditions, provide the corresponding pyrrolo [1,2-a]quinoxalines. 7 Sharma et al reported the one-pot synthesis of 4-aryl pyrrolo [1,2-a]quinoxalines from 1-(2-aminophenyl)pyrroles and aromatic aldehydes by a modified Pictet-Spengler reaction using cyanuric chloride.…”
mentioning
confidence: 99%